2022
DOI: 10.1021/acsami.2c17544
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming Cytosolic Delivery Barriers of Proteins Using Denatured Protein-Conjugated Mesoporous Silica Nanoparticles

Abstract: Intracellular delivery of therapeutic proteins has increased advantages over current small-molecule drugs and gene therapies, especially in therapeutic efficacies for a broad spectrum of diseases. Hence, developing the protein therapeutics approach provides a needed alternative. Here, we designed a mesoporous silica nanoparticle (MSN)-mediated protein delivery approach and demonstrated effective intracellular delivery of the denatured superoxide dismutase (SOD) protein, overcoming the delivery challenges and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 65 publications
0
11
0
Order By: Relevance
“…Subsequently, we employed HE staining to scrutinize the histology of tissues from the heart, liver, spleen, lung, and kidney (Figure B). The histological examination of the tissues unveiled no notable distinctions between the experimental and control groups . Importantly, the HAp–FeCr treatment did not induce any pathologically evident harm to the examined organs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, we employed HE staining to scrutinize the histology of tissues from the heart, liver, spleen, lung, and kidney (Figure B). The histological examination of the tissues unveiled no notable distinctions between the experimental and control groups . Importantly, the HAp–FeCr treatment did not induce any pathologically evident harm to the examined organs.…”
Section: Resultsmentioning
confidence: 99%
“…The histological examination of the tissues unveiled no notable distinctions between the experimental and control groups. 50 Importantly, the HAp−FeCr treatment did not induce any pathologically evident harm to the examined organs. Notably, the spleen in each experimental group exhibited a number of lymphocytes comparable to the control group, signifying the absence of any abnormal immune responses.…”
Section: Evaluation Of In Vivo Biosafetymentioning
confidence: 90%
“…A survey of European consumers found that NPs were present in over 2300 commercial products. Titanium dioxide (TiO 2 ), aluminum oxide (Al 2 O 3 ), silicon oxide (SiO 2 ), carbon nanotubes, ZnO, ferrous oxide, ceric oxide, Au, and CuS are common NPs [82][83][84][85][86][87]. The majority of nanoparticles (NPs) exhibit biocompatibility and chemical inertness, with examples such as gold and titanium dioxide [88].…”
Section: Semiconductor-and Carbon-based Nanomaterialsmentioning
confidence: 99%
“…The use of NPs to deliver proteins directly within cells is considered an effective alternative to gene therapy. 249,250 Protein delivery can directly restore the function of the end product without genetic alteration of the target cells 251,252 and therefore without the risk factors of gene therapy, such as genetic interference and uncontrollable gene expression during recombination. 253 Lipid nanoparticle-based drug delivery systems have been extensively explored for protein delivery.…”
Section: Nps For Gene Editing Proteins Deliverymentioning
confidence: 99%